Development of Lightweight 200‐W Direct Methanol Fuel Cell System for Unmanned Aerial Vehicle Applications and Flight Demonstration1. Issue 5 (20th October 2014) - Kang, K.; Park, S.; Cho, S.‐O.; Choi, K.; Ju, H.; Jones, Deborah; Jaouen, Frederic; Taillades‐Jacquin, Mélanie; Bucheli, Olivier
Abstract A lightweight 200‐W direct methanol fuel cell (DMFC) stack was developed to power a small‐scale unmanned aerial vehicle (UAV). To reduce the weight and volume of the DMFC stack, carbon‐composite bipolar plates were fabricated using natural graphite, phenolic resin, and carbon black. In addition, lightweight end plates, bolts, and nuts were fabricated using polyetheretherketone (PEEK) materials. The lightweight DMFC stack, which was designed for small UAV operating under cruising conditions, consisted of 33 cells, in which membrane‐electrode assemblies (MEAs) with active area of 88 cm2 were stacked with the composite bipolar plates. The DMFC stack was first evaluated under various methanol feed concentrations. It produced a maximum power of 251 W at 13.4 V and 71.3 °C under methanol feed concentration of 2 M. Thereafter, the DMFC stack was integrated with a Li‐polymer battery as an auxiliary power source, and the load‐sharing characteristics of the UAV propulsion system were tested under actual flight mode comprising takeoff, cruising, and landing. The flight test results showed that the lightweight DMFC stack successfully delivered full power for cruise flight, whereas the battery provided the additional power required during takeoff. This work successfully demonstrated that the DMFC technology can be applied to small‐scale UAVs.